A prospective study examining the impact of uniportal video‐assisted thoracic surgery on the short‐term quality of life in patients with lung cancer. Issue 3 (22nd January 2020) - Xu, Guang‐wen; Xie, Ming‐ran; Wu, Han‐ran; Xiong, Ran; Li, Cai‐wei; Xu, Shi‐bin; Xu, Mei‐qing; Li, Tian
Abstract : Background: The aim of this study was to evaluate the effect of uniportal and three‐portal VATS in lung cancer patients on the postoperative short‐term quality of life (QOL). Methods: A single‐center, prospective, nonrandomized study was performed on patients who underwent uniportal or three‐portal video‐assisted thoracoscopic surgery (VATS) lobectomy and systemic mediastinal lymph node dissection. QOL was measured before surgery at baseline and at one, two, four, and eight weeks after the operation. The measured data of normal distribution were indicated by the mean ± standard deviation, the independent sample t ‐test was used among the groups, and the χ2 test was used to compare the counting. Non‐normal distribution of the measurement data was carried out using the Mann‐Whitney test. Results: Preoperative functional areas, symptom areas and overall health scores were similar in the two groups. The physical, role, emotional and social functions and overall health status of the uniportal group were significantly higher than those of the three‐portal group in postoperative time. The score of symptom field was higher in one week after operation, the score of two, four and eight weeks decreased gradually, but it was still above the preoperative level, and the fatigue and pain of the uniportal group were significantly lower than that of the three‐portal group. Conclusion: The advantages of uniportal VATS include a shorter hospital stay, more rapid recovery and superior cosmetic results compared to three‐portal VATS. Additionally, uniportal VATS is superior to three‐portal thoracoscopic surgery in terms of the immediate postoperative short‐term QOL.